Cross-sectional and prospective associations between children's eating behavior and visceral fat area and trunk fat mass - Wang, Youxin; Shen, Fangjing; Zhang, Pingping; Xu, Miao; Qiu, Danqi; Wang, Hui; Li, Li (Frontiers in Pediatrics, 2024)
BackgroundUnderstanding children's eating behaviors is crucial for elucidating the etiology of childhood obesity. However, the relationship between these behaviors and abdominal fat accumulation remains poorly understood. This study aims to investigate this association in primary school children.MethodsThis study included 1,475 children aged 8–10 years in Ningbo, China. Body composition was measured both at baseline (September 2022) and after 9 months of follow-up (June 2023). Primary caregivers completed the Children's Eating Behavior Questionnaire (CEBQ). A mixed-effects linear model was applied to analyze the relationships between children's eating behaviors and body composition.ResultsGreater visceral fat area (VFA) was associated with greater slowness in eating [β = 0.25 (0.02, 0.49)], greater food responsiveness [β = 0.29 (0.14, 0.43)], increased emotional undereating [β = 0.35 (0.17, 0.54)], and more emotional overeating [β = 0.21 (0.02, 0.39)]. Children with greater trunk fat mass (TrFM) tended to have greater food responsiveness [β = 0.02 (0.01, 0.03)] and greater enjoyment of food [β = 0.01 (0.00, 0.03)], increased emotional undereating [β = 0.02 (0.01, 0.03)] and emotional overeating [β = 0.02 (0.00, 0.03)]. Prospectively, positive correlations were observed between VFA and food responsiveness [β = 0.18 (0.02, 0.35)], as were emotional undereating [β = 0.31 (0.10, 0.52)] and emotional overeating [β = 0.24 (0.03, 0.46)]. Similarly, TrFM was positively correlated with food responsiveness [β = 0.02 (0.00, 0.03)], enjoyment of food [β = 0.02 (0.00, 0.04)], emotional undereating [β = 0.02 (0.01, 0.04)] and emotional overeating [β = 0.02 (0.01, 0.04)].ConclusionsOur findings suggest that eating behaviors are significantly associated with abdominal fat accumulation in primary school children. Addressing specific eating behaviors may be crucial in mitigating abdominal fat and its related health risks.